P3-S7.02 Performance of a point-of-care diagnostic for Bacterial Vaginosis among young reproductive age women in Mysore, India. (10th July 2011) - Ravi, K; Kotian, S; Rao, K; Selezneva, J; Srinivas, V; Krupp, K; Madhivanan, P
Abstract : Background: Bacterial vaginosis (BV) remains the most common cause of abnormal vaginal discharge in Indian women of reproductive age and is associated with increased susceptibility to HIV/STI and preterm delivery. Diagnosis of BV in resource-poor settings is often overlooked; there is a need for cheap, rapid, objective point-of-care diagnostic test. Methods: Vaginal swabs were collected from women attending a women's health clinic. Women over the age of 18 with a pH of over 4.5 were invited to participate in the study. BV was diagnosed on the basis of the Nugent score, the Amsel clinical criteria, and results of OSOM BVBlue test independently by study clinician and laboratory personnel who were blinded to the results of the other tests. Results: From August 2009 to May 2010, 313 participants were enrolled. BV prevalence was 45.1% (95% CI 41.5% to 52.8%) according to Nugent score. When compared with the Nugent score, the sensitivity, specificity, positive predictive value, negative predictive value for Amsel clinical criteria was 61.9%, 88.3%, 81.5%, 73.7%; and for BVBlue it was 38.1%, 92.7%, 82.1%, 63.9% respectively. The performance of BVBlue can be increased if it is combined with "Whiff test where the sensitivity increases to 64.4%, sensitivity 85.6%, PPV 79.3% and NPV 73.8%". Conclusions: These results highlight the importance of systematic evaluation of rapid test kits as a low-cost alternative to laboratory diagnosis in resource-constrained settings. The BVBlue test is a simple, rapid, and objective test for the diagnosis of BV and has the potential to facilitate prompt diagnosis and appropriate treatment of BV in the absence of microscopy.